2014
DOI: 10.1016/j.toxicon.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Crotoxin from Crotalus durissus terrificus snake venom induces the release of glutamate from cerebrocortical synaptosomes via N and P/Q calcium channels

Abstract: Crotoxin (Crtx), the main toxin in the venom of Crotalus durissus terrificus snake, is a heterodimer with a basic subunit, CB, and an acidic subunit, CA. CB is a phospholipase A2 that depends on CA to specifically bind to the cell membrane. This toxin acts in the central nervous system (CNS) causing chronic seizure effects and other cytotoxic effects. Here, we report its action on glutamate release in rat cerebral cortex synaptosomes. Aiming at a better understanding of the mechanism of action of Crtx, calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…As a consequence, Ca 2 + influx may promote activation of SNARE proteins favouring the fusion probability of synaptic vesicles with the plasma membrane and, thereby, the transmitter exocytosis. Supporting this hypothesis, recently Lomeo et al (2014) showed the involvement of Ca 2 + in the facilitatory effect of CTX on transmitter release in glutamatergic synapses. It is clear that the early facilitatory phase of the CTX effect on transmitter release is not mediated by an enzymatic activity, since inhibition of PLA 2 activity by reducing the temperature, removal of calcium from the extracellular medium and its replacement by strontium were not able to abolish this transient facilitatory phase (Su and Chang, 1984;Rowan and Harvey, 1988;.…”
Section: Discussionmentioning
confidence: 79%
“…As a consequence, Ca 2 + influx may promote activation of SNARE proteins favouring the fusion probability of synaptic vesicles with the plasma membrane and, thereby, the transmitter exocytosis. Supporting this hypothesis, recently Lomeo et al (2014) showed the involvement of Ca 2 + in the facilitatory effect of CTX on transmitter release in glutamatergic synapses. It is clear that the early facilitatory phase of the CTX effect on transmitter release is not mediated by an enzymatic activity, since inhibition of PLA 2 activity by reducing the temperature, removal of calcium from the extracellular medium and its replacement by strontium were not able to abolish this transient facilitatory phase (Su and Chang, 1984;Rowan and Harvey, 1988;.…”
Section: Discussionmentioning
confidence: 79%
“…Other studies have showed that presynaptic toxins from snake venoms, in general, can enter into the lumen of synaptic vesicles following endocytosis and hydrolyze phospholipids from the inner leaflet of the membrane [ 79 ]. Remarkably, it was demonstrated that the CB subunit can be internalized in cerebrocortical synaptosomes, independently of the presence of CA or of its catalytic activity [ 80 ]. Finally, it was recently demonstrated that CTX can interact with nicotinic acetylcholine receptors [ 81 ] and that the CB subunit can interact with, and be an allosteric modulator of, cystic fibrosis transmembrane regulator (CTRF) chloride channel [ 82 ].…”
Section: Crotoxin a Heterodimeric Neurotoxin From Crotamentioning
confidence: 99%
“…Synergisms are mostly reported for major toxins in rattlesnake venoms [ 73 ]. A notable example of synergism through complex formation (mechanism 3) is crotoxin, a lethal neurotoxin from C. durissus terrificus , by two subunits: an acidic subunit component A (CA or crotapotin) and a basic subunit component B (CB) [ 109 , 115 , 116 , 180 , 181 ]. CB is identified as a basic PLA 2 with phospholipase activities and low toxicity, while the CA component is said to be a small acidic, nonenzymatic, nontoxic subunit [ 73 , 181 ].…”
Section: Discussionmentioning
confidence: 99%